Tissue Thickness Effects on Immunohistochemical Staining Intensity of Markers of Cancer. Issue 5 (May 2019) - McCampbell, Adrienne S.; Raghunathan, Varun; Tom-Moy, May; Workman, Richard K.; Haven, Rick; Ben-Dor, Amir; Rasmussen, Ole F.; Jacobsen, Lars; Lindberg, Martin; Yamada, N. Alice; Schembri, Carol
Abstract : High-quality patient samples are required for reliable immunohistochemistry test outcomes that provide a significant benefit for patient care. Among the preanalytic variables in tissue handling, tissue thickness is thought to be easily controlled; however, whether the thickness of the tissue effects the staining intensity for antibody immunohistochemistry has not been quantitatively demonstrated. To investigate, we cut multiblock tissue sections of tonsil, liver, and kidney at 2, 4, 6, and 8 μm thicknesses. Interferometry measurements of the sectioned paraffin showed a <1 μm variation within a preset microtome thickness. Sections were then immunostained with antibodies targeting different cellular localizations; Ki-67 and BCL6 (nuclear), CD7 (membranous), and cytokeratin (cytoplasmic). A pathologist annotated regions of interest for each marker and performed brightfield and whole-slide visual scoring. Then a pixel-wise processing algorithm determined intensity of each pixel in these regions of interest and binned them into predetermined 0, 1+, 2+, or 3+ intensities. Visual scores from brightfield and whole-slide images were highly correlated to the percentage of pixels in each intensity bin. A stepwise increase was observed in pathologist scores and algorithmically defined percentage of pixels in each bin with increasing thickness demonstrating that changes in preset section thickness impacts staining intensity. The use of tissue thickness outside vendors' recommendations might change the intensity including the proportion of positive and negative cells and eventually the overall diagnosis outcome. Therefore, we recommend that tissue be consistently cut within the middle of thickness range specified by the assay manufacturer. Abstract : Supplemental Digital Content is available in the text.